2010
DOI: 10.2478/v10237-011-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Focus of Attention and Verbal Instructions: Strategies of Elite Track and Field Coaches and Athletes

Abstract: I t is well documented that directing attention externally enhances motor skill learning and performance under controlled experimental conditions. What is not well understood is how verbal instructions (VI) and feedback provided by coaches in authentic environments influences athletes' focus of attention. Thus, the purpose of this study was to investigate the type of VI and feedback provided by experienced coaches during practice, and how this information influenced elite athletes' focus of attention during co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
84
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 9 publications
11
84
1
2
Order By: Relevance
“…Given the relative dearth of studies examining attentional focus effects in children, and the fact that instructions given in practical settings are typically body-related and therefore induce an internal focus (Porter, Wu, & Partridge, 2010), it seemed important to further examine the influence of different types of instructions on sport skill learning in children. Studies have demonstrated differences in motor learning between children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Given the relative dearth of studies examining attentional focus effects in children, and the fact that instructions given in practical settings are typically body-related and therefore induce an internal focus (Porter, Wu, & Partridge, 2010), it seemed important to further examine the influence of different types of instructions on sport skill learning in children. Studies have demonstrated differences in motor learning between children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we investigated if elite coaches use strategies consistent with the motor learning and control literature, namely, principles of practice variability and contextual interference. Based on the findings of Williams and Ford (2009) and Porter et al (2010), it was hypothesized that elite coaches do not use methods consistent with the motor learning and control literature to develop accuracy. The results of the present study partially supported this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, the purpose of this study was to investigate how elite horizontal jump coaches develop the accuracy component of the horizontal jump events in track and field and to examine whether or not the coaches utilized principles of practice variability and contextual interference found within the motor learning and control literature. Based on previous findings (Porter, Wu, & Partridge, 2010;Williams & Ford, 2009) we hypothesized that elite horizontal coaches will not utilize methods for developing accuracy that are consistent with the practice variability and contextual interference literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent criticisms of past research on augmented feedback, along with the lack of separation of KR and KP, and the lack of retention or transfer tests, are about the use of "artificial" laboratory tasks and the lack of consideration of the characteristics of motor skills. It has been argued that the generalized principles of augmented feedback from the laboratory with one-dimensional tasks may not apply well to more complex real-world settings [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and that skills with different characteristics need different types of feedback information for effective learning. The number of explanation for the lack of effectiveness on skill acquisition may be due to overly complex information presented, failure to provide critical feedback about the skill and not providing enough information for error detection [13].…”
Section: Introductionmentioning
confidence: 99%